Malawi Economy: Population, GDP, Inflation, Business, Trade, FDI, Corruption - The Heritage Foundation (2022)
Learn more about the Malawi economy, including the population of Malawi, GDP, facts, trade, business, inflation and other data and analysis on its economy from the Index of Economic Freedom published by The Heritage Foundation.
KerkoCite.ItemAlsoKnownAs: 2339240:V32U7VEA 2405685:WDLTPYAE

Language policy in Ghana and Malawi: differing approaches to multilingualism in education - Reilly, Colin; ResCue, Elvis; Chavula, Jean Josephine (Journal of the British Academy, 2022)
Despite substantial international evidence that children learn best in a language which they understand, language-in-education policies in much of Africa do not effectively accommodate the range of languages found in the classroom, instead prescribing dominant national languages and/or colonial languages such as English. Further, these language policies continue to reflect a monoglossic conceptualisation of languages and do not adequately account for the multilingual repertoires of individuals and communities. They do not reflect an understanding of the ways in which multilingual language practices could be harnessed for education. This article provides a comparative overview of the policy context in Malawi and Ghana, at the levels of legislation, practice, and attitudes. Through interviews, questionnaires, classroom observations, and classroom recordings in primary schools, we highlight the multilingual realities of educational spaces in each country. We highlight that, despite different sociolinguistic and legislative contexts, there are similarities between these contexts which emerge as important factors when considering multilingualism within education.
KerkoCite.ItemAlsoKnownAs: 10.5871/jba/010s4.069 2405685:2QFJWC3E 4042040:SBXDCXLU

2022 Malawi Education Statistics Report (EMIS) - Malawi Ministry of Education (Government of Malawi, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:QDQNJ628 2405685:PVLSA2PA

Malawi Social Cash Transfer Programme Strategic Plan 2022 - 2027 - Government of Malawi; UNICEF (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:NNGIVX4W 2405685:XXEGUPKH

Improving teaching and learning mathematics in Malawi primary schools: a review of reforms, interventions, successes and challenges - Kazima, Mercy; Longwe, Justina; Gobede, Fraser (Journal of Applied Learning & Teaching, 2022)
KerkoCite.ItemAlsoKnownAs: 10.37074/jalt.2022.5.S2.3 2339240:4FKUR5CB 2405685:EDYLSVNI

Global Health | Malawi | U.S. Agency for International Development - USAID (2022)
Over the last two decades, Malawi has achieved dramatic gains in most health indicators by focusing on the improved delivery of essential health services. Malawi is one of a few sub-Saharan African countries that achieved Millennium Development Goal (MDG) 4 for child survival by 2015. The Government of Malawi (GoM) reduced maternal mortality by 53 percent between 1990 and 2013, and increased the contraceptive prevalence rate from 7.4 in 1992 to 42 percent in 2010.
KerkoCite.ItemAlsoKnownAs: 2339240:UPMFQ54I 2405685:9QFUUNDN

USAID Announces $74 Million for Early Grade Reading in Malawi | Press Release - USAID (U.S. Agency for International Development, 2022)
The U.S. government, through the U.S. Agency for International Development (USAID), is supporting Malawi’s vision for early grade literacy through the new Next Generation (NextGen) early grade reading project. This investment of $74 million over the next five years, subject to appropriations, will improve the delivery of high-quality early grade reading instruction in all of Malawi’s over 5,700 public primary schools nationwide. Since 2015, the U.S. government has invested more than $136 million in Malawi’s early grade reading efforts.
KerkoCite.ItemAlsoKnownAs: 2339240:VVQUGZN4 2405685:MGLZTU2M

The World Bank in Malawi - World Bank (World Bank, 2022)
The World Bank Group supports Malawi’s efforts to reduce poverty and promote economic growth by working with the government, development partners, and civil society.
KerkoCite.ItemAlsoKnownAs: 2339240:824ICBPH 2405685:MR9UQSNI

Two-year RCT of EdTech in Malawi - Levesque, Karen; Bardack, Sarah; Chigeda, Antonie; Bahlibi, Abraham; Winiko, Symon (2022)
Malawi’s primary education system has been challenged to provide quality learning in the face of expanding enrollment. To address poor learning outcomes, the Ministry of Education piloted use of onebillion’s onecourse software in about 100 schools. Initial studies of onecourse conducted over 8 weeks to 8 months produced significant effect sizes in math and literacy, although absolute gains were modest. To measure longer-term impacts, Imagine Worldwide conducted a 2-year efficacy randomized controlled trial in two Malawi schools. Despite COVID-related school closures, onecourse produced statistically significant impacts in literacy and math. Further, the 13 months of (interrupted) intervention produced larger effect sizes and higher rates of attaining emergent or fluent reading and math benchmarks than the prior 8-month study.
KerkoCite.ItemAlsoKnownAs: 2339240:J8CBHM6Z 2405685:WNI92EHA
Keywords: ⛔ No DOI found

Returning to school after COVID-19 closures: Who is missing in Malawi? - Kidman, Rachel; Breton, Etienne; Behrman, Jere; Kohler, Hans-Peter (International Journal of Educational Development, 2022)
During the early stages of the COVID-19 pandemic, almost all countries implemented school closures to prevent disease transmission. However, prolonged closures can put children at risk of leaving school permanently, a decision that can reduce their long-term potential and income. This study investigated the extent to which the COVID-19 pandemic and associated school closures reduced school attendance in Malawi, a low-income African country. We used longitudinal data from a cohort of adolescents interviewed before (2017/18; at age 10–16) and after (2021; at age 13–20) the pandemic school closures. Of those students who had been attending school prior to school closures, we find that 86% returned when schools re-opened. Dropouts were more pronounced among older girls: over 30% of those aged 17–19 did not return to school. This resulted in further lowering the gender parity index to the greater disadvantage of girls. We also found that students already lagging behind in school were more likely to dropout. Thus, our data suggest that the COVID-19 pandemic has magnified gender inequalities in schooling, at least partially erasing recent progress towards inclusive education. Urgent investments are needed to find and re-enroll lost students now, and to create more resilient and adaptable educational systems before the next pandemic or other negative shock arrives.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2022.102645 2339240:GY9BBMLF 2405685:QFFZJ8XM
Keywords: Adolescents; COVID-19; Child marriage; Education; Pregnancy; School closures

Transformational Empowerment of Adolescent Marginalised Girls in Malawi - da Silva, Carol; Laesecke, Anne; Murray, Matthew; Salicath; Wang, Erica (Girls' Education Challenge, UK Aid, 2022)
KerkoCite.ItemAlsoKnownAs: 2405685:EDU4BFPR

Postgraduate Programmes September 2022 Intake - University of Malawi (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:FM6Y39Y5 2405685:TRJIVM2S

Joint Sector Review Resources – Presentations - Malawi Ministry of Education (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:8QQZ2C4K 2405685:6L23TW3P

Zomba District (Wikipedia, 2022)
Zomba District is one of twelve districts in the Southern Region of Malawi, surrounded by the districts of Chiradzulu, Blantyre, Mulanje, Phalombe, Machinga, Balaka and the Republic of Mozambique to the east. The total land area is 2,363 km2, representing three percent of the total land area of Malawi. The capital is Zomba.
Page Version ID: 1069176198

Malawi Education Rights - UNESCO (UNESCO, 2022)
UNESCO is the United Nations Educational, Scientific and Cultural Organization. It seeks to build peace through international cooperation in education, the sciences, culture and communication. UNESCO’s programmes contribute to the achievement of the Sustainable Development Goals defined in Agenda 2030, adopted by the UN General Assembly in 2015. Serving as a laboratory of ideas, UNESCO helps countries adopt international standards and manages programmes that foster the free flow of ideas and knowledge sharing. In this spirit, it develops educational tools to help people live as global citizens free of hate and intolerance. UNESCO works so that each child and citizen has access to quality education. By promoting cultural heritage and the equal dignity of all cultures, it strengthens bonds among nations. UNESCO fosters scientific programmes and policies that support development and cooperation. UNESCO stands up for freedom of expression, as a fundamental right and a key condition for democracy and development.
KerkoCite.ItemAlsoKnownAs: 2339240:TDR9FIDZ 2405685:RPICI3GC

Implementing DREAMS Programming in Malawi - Bantwana World Education Initiative (2022)
KerkoCite.ItemAlsoKnownAs: 2405685:CNBT7I8Y

Teaching and Learning Materials in Malawi - Kendall, Nancy; Samati, Madalo (Global Education Monitoring Report, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:WA4Q9XHZ 2405685:NQ65CGEN

Coronavirus disease (COVID-19) | UNICEF Malawi - UNICEF (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:KA2U5H5L 2405685:RKXDY3RJ

Guidance Note on Education Data Mapping in Sub-Saharan Africa: Moving from theory to practice - Selwaness, Irene; Adam, Taskeen; Lawson, Laté; Heady, Lucy (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6339212 10.53832/edtechhub.0096 2339240:VJZWBP65 2405685:6JLQ7UC6 2405685:KQUDWCXC
Keywords: _r:AddedByZotZen

Cohort 3 Digital Skills Training Completion | Digital Malawi - Ntha Foundation (Ntha Foundation, 2022)
The evaluation and assessment process of the first phase of the Digital skills training is taking place at the Kwathu Innovation and Creative Centre hub this week.
KerkoCite.ItemAlsoKnownAs: 2339240:AJPH8VMP 2405685:VE4K65UC

EdTech supporting sex education for students in Malawi Global EdTech - Global EdTech (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:QTMLVWGG 2405685:ICAKNQAC

Achieving gender and youth inclusivity in Malawi through Productive Alliances - Botha, Blessings (2022)
When I was young, there was a common adage “youth are the leaders of tomorrow,” and I was always looking forward, with optimism that this tomorrow will indeed come one day.
KerkoCite.ItemAlsoKnownAs: 2339240:E7DG7FBL 2405685:8PTK8M68

Two-year RCT of EdTech in Malawi: Impacts of a 2-year education technology program on early primary learning in Malawi amid disruptions due to COVID-19 - Levesque, Karen; Bardack, Sarah; Chigeda, Antonie; Bahlibi, Abraham; Winiko, Symon (2022)
KerkoCite.ItemAlsoKnownAs: 2405685:ZDDVIBT7

Malawi - Adolescents Out Of School (% Of Lower Secondary School Age) - 2022 Data 2023 Forecast 1999-2019 Historical - Trading Economics (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:B2EZI8AS 2405685:TDW3BSQ3

DRAFT Technical Report: Impacts of a 2-year EdTech program on early primary learning in Malawi amid disruptions due to COVID-19 - Imagine Worldwide (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:IHETD9DX 2405685:M4C6ZJ6J

Guidance on Pre-Assessment for Establishing E-Learning Centres - AlSheikh Theeb, Thaer; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5813529 10.53832/edtechhub.0084 2405685:DPWSAA9Z
Keywords: _r:AddedByZotZen

Experiment Types for EdTech - Rahman, Asad; Carter, Alice; WambûiKuria, Catherine; Mbugua, Ciku; Simpson, Lea; Kably, Nathan (EdTech Hub, 2022)
An EdTech Hub sandbox fast-tracks promising EdTech interventions by providing funding, tools, and access to evidence. It provides a space for partners to test and grow ideas in conditions of uncertainty. Since 2020, EdTech Hub has worked with partners in eight countries to test and grow EdTech based on our sandbox methodology. When testing and growing EdTech, this tool provides a non-exhaustive list of ways to design and run experiments. Keywords: sandbox; lean startup; lean impact; experiments; validation; prototype An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7245945 ZenodoArchiveConcept: 7245944 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7245945 10.53832/edtechhub.0128 2405685:X8MUXS39
Keywords: _r:AddedByZotZen

Session 4: How can I rapidly upskill my large teacher workforce? - Koomar, Saalim; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341501 ZenodoArchiveConcept: 7341500 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341501 10.53832/edtechhub.0138 2405685:E7C9MN3V
Keywords: _r:AddedByZotZen

Session 6: How do I ensure my EdTech investments are cost-effective? - Chuang, Rachel; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341519 ZenodoArchiveConcept: 7341518 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341460 10.5281/zenodo.7341519 10.53832/edtechhub.0140 2405685:CUFS8JJE 2405685:CWKPJR8R
Keywords: _r:AddedByZotZen

Session 5: How can I use EdTech to ensure that students are provided with quality educational content at the right level? - Mazari, Haani; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341509 ZenodoArchiveConcept: 7341508 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341509 10.53832/edtechhub.0139 2405685:NUTI6KUS 2405685:PPRW2NTQ
Keywords: _r:AddedByZotZen

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5604677 10.5281/zenodo.5761966 10.53832/edtechhub.0069 2405685:CPP3A2WM 2405685:DM8N3E8E 2405685:PXUQJZTH
Keywords: Helpdesk Response; _r:AddedByZotZen

Education Statistics Report - Ministry of Education (Government of the Republic of Malawi, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:A5HSJY46 2405685:5VPNL7IE

Should we paint all classroom roofs white to improve learning in Tanzania? - Proctor, Jamie (2022)
A growing literature base has developed from Global North contexts, showing a clear link between classroom temperature and student learning outcomes. However, very little evidence shows how this impact translates to low- and middle-income countries (LMICs), where average classroom temperatures are often high. The hypothesis for the research was that classroom temperatures in Tanzania are high and that a white-paint-cool-roof intervention would help mitigate these high temperatures. This study includes a literature review to understand the classroom policy in Tanzania, establish links between temperature and learning, and assess temperature retrofit options. Following this, the study presents the results of an experiment to trial a white-paint cool roof against a blue-paint roof and an unpainted control roof. Finally, data analysis predicts the intervention effects over an entire year and the subsequent impact on learning outcomes. The learning outcomes analysis includes a cost-effectiveness analysis using the Learning-Adjusted Years of Schooling (LAYS) metric. Empirical evidence of temperatures inside classrooms in Dar Es Salaam suggests that the temperature often exceeds 40℃. Literature searches indicate that this is the first time classroom air temperatures have been recorded and published for East Africa. The experiment involved using a low-cost retrofit intervention to reduce temperature – by painting the classroom roof blue or white over eight days. Results showed that the White Paint Intervention (WPI) reduced the temperature by around 3.7℃ over the course of the school day and up to a maximum of 5℃. The WPI was roughly twice as effective as the Blue Paint Intervention at reducing interior air temperatures. The WPI results were then modelled to estimate the classroom temperature reduction over a year, based on the assumed 3.5℃ reduction. Finally, using estimates from the existing literature, the learning impact of the intervention was calculated. The results suggest that using the WPI intervention can improve learning by 7.1%, which translates to an estimated 3.2 LAYS per classroom per year, at a cost-effectiveness of 5.3 LAYS per USD100. The paper shows that the impact of high temperatures in classrooms is likely undermining the funding currently channelled to improve learning outcomes in the region. Further, a WPI retrofit intervention is effective at reducing classroom temperatures in Tanzania. Due to climate-change-induced temperature increases, the intervention effectiveness is likely to increase over the coming decades. This paper was submitted as a dissertation in fulfilment of an MSc in Sustainability and Adaptation in the Built Environment at the Centre for Alternative Technology, Machynlleth, Powys (Wales)
ZenodoArchiveID: 7139243 ZenodoArchiveConcept: 7139242 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7139243 10.53832/edtechhub.0122 2405685:Z8B66R9X
Keywords: _r:AddedByZotZen

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6924683 10.53832/edtechhub.0102 2339240:LDWT8LYC 2405685:JPXVGB3A 2405685:MNMTIMGA 2405685:Q9J54HFA
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 5: Final report - Groeneveld, Caspar; Michels, Guillaume; Kaye, Tom (EdTech Hub, 2022)
In 2021, the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE), and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fifth and final report on the development of a proof of concept for the Regional Learning Hub. We recommend beginning with this document and then moving to any of the remaining four reports, depending on your interest: Inception report; User research; Skills taxonomy; Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5795656 10.53832/edtechhub.0079 2405685:5XBMPDX6
Keywords: _r:AddedByZotZen

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 2: Insights from user research - Rahman, Asad; Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the second of five reports on the development of a proof of concept for the Hub. It provides a summary of user research undertaken for the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest. Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803107 10.53832/edtechhub.0076 2405685:CI5UZ5R4 2405685:HU5IFEK9
Keywords: _r:AddedByZotZen

How EdTech Can Be Used to Help Address the Global Learning Crisis: A Challenge to the Sector for an Evidence-Driven Future - Hollow, David; Jefferies, Kate (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0115 2339240:3KZX9ARU 2405685:BBQE9QUM 2405685:UUDK52LQ 2405685:YB52PCMQ
Keywords: ⛔ No INSPIRE recid found